ANALYSIS OF THE INFLUENCE OF PRODUCT QUALITY, STORE ATMOSPHERE AND EXPERIENTIAL MARKETING ON REPATRONAGE INTENTIONS THROUGH BRAND AWARENESS AS AN INTERVENING VARIABLE - Imron, Ali; ariyanti, rizka (Universitas PGRI Semarang, 2023)
The purpose of this study was to determine the effect of Product Quality, Store Atmosphere and Experiential Marketing on Repatronage Intentions through Brand Awareness as an Intervening variable. This study used a sample of 100 respondents, namely consumers at the Yogya Department Store, Pemalang. The sample used was purposive sampling technique. The testing in this study was carried out using the method multiple linear regression analysis. The results of this study obtained there is a significant influence between variables Product Quality, Atmosphere, Experiential Marketing to Repatronage Intentions. Furtheremore, there is a significant influence between Product Quality, Atmosphere, Experiential Marketing on Repatronage intentions through Brand Awarenes as an intervening variable.